Unusual number of Southern Rockhopper Penguins, Eudyptes chrysocome, molting and dying along the Southern Patagonian coast of Argentina: pre-molting dispersion event related to adverse oceanographic conditions? - Morgenthaler, Annick (2018)
The annual molt of Southern Rockhopper Penguins, Eudyptes chrysocome, usually takes place at their colonies after a pre-molting foraging trip. In 2016, an unusual number of Rockhopper Penguins was found molting, and in part subsequently dying, along the southernmost portion of the Argentine coast, far from the main colonies. To report the extent of this dispersion and mortality event, a survey was conducted between February and May 2016 along the southern Patagonian coast. A total of 1039 molting Rockhopper Penguins were reported. The mortality, mainly attributed to starvation, varied between 40 and 89%, according to sites. Furthermore, as adverse oceanographic conditions are known to affect prey availability and penguin’s survival, chlorophyll a concentrations (as a primary productivity index) and sea surface temperatures were analyzed at main foraging grounds. The results showed lower chlorophyll a and sea surface temperature values close to the main colonies during 2016 (compared to average 2003–2015). Although these values alone cannot explain such mortality (as similar low values already occurred in some of the previous year without inducing mortality events), our results support the hypothesis of a reduction in primary productivity close to the main colonies prior to the molt, inducing penguins to move towards more distant foraging grounds, which finally led them to molt later and away from their colonies. Although the oceanographic processes were not fully understood, this event highlights the serious effects that unusual conditions prior to molting can pose on the survival of this endangered penguin, in a context of climate variability.